2013
DOI: 10.1111/asj.12108
|View full text |Cite
|
Sign up to set email alerts
|

Multiple marker effects of single nucleotide polymorphisms in three genes, AKIRIN2, EDG1 and RPL27A, for marbling development in Japanese Black cattle

Abstract: Marbling in beef, measured by Beef Marbling Standard (BMS) number, is an economically important trait for beef cattle breeding and markets in Japan. We previously detected three single nucleotide polymorphisms (SNPs) associated with BMS number of Japanese Black in Oita prefecture: c.*188G>A in AKIRIN2, g.1471620G>T in EDG1 and g.3109537C>T in RPL27A. Here, we carried out single and multiple marker association analyses for the three SNPs in a different commercial Japanese Black population of 892 genotyped anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…The very high frequency of G allele in the present study was also detected in Japanese Shorthorn (0.975 to 0.981), Holstein (0.790) and Brown Swiss cattle (0.787) (Watanabe et al 2011). In contrast, the frequency of G allele tends to be less in Japanese Black cattle (0.262 to 0.568) (Sasaki et al 2009;Watanabe et al 2011;Sukegawa et al 2014) and Japanese brown (0.389 to 0.430) (Watanabe et al 2011). In the SNP of EDG1:c.-312A>G, all individuals of Bali cattle studied were detected to have AA genotype (100%) and consequently A allele was found to be fixed (1.000).…”
Section: Genetic Polymorphismsupporting
confidence: 59%
See 2 more Smart Citations
“…The very high frequency of G allele in the present study was also detected in Japanese Shorthorn (0.975 to 0.981), Holstein (0.790) and Brown Swiss cattle (0.787) (Watanabe et al 2011). In contrast, the frequency of G allele tends to be less in Japanese Black cattle (0.262 to 0.568) (Sasaki et al 2009;Watanabe et al 2011;Sukegawa et al 2014) and Japanese brown (0.389 to 0.430) (Watanabe et al 2011). In the SNP of EDG1:c.-312A>G, all individuals of Bali cattle studied were detected to have AA genotype (100%) and consequently A allele was found to be fixed (1.000).…”
Section: Genetic Polymorphismsupporting
confidence: 59%
“…The genotype of AKIRIN2:c.*188G>A detected in Bali cattle were the GG (99.2%) and GA (0.8%), while AA genotype was not detected. The GG genotype was found to be the most frequent in Bali cattle, but not in Japanese Black and Korean cattle where the AG genotype was the most frequent genotype (48.0 to 52.3% and 64.7 to 73.2%, respectively) (Sasaki et al 2009;Watanabe et al 2011;Kim et al 2013;Sukegawa et al 2014). The G allele was to be the predominant allele in Bali cattle (0.996).…”
Section: Genetic Polymorphismmentioning
confidence: 87%
See 1 more Smart Citation
“…Currently, Akirin2 has been reported to be located within genomic region of a quantitative trait locus for marbling, and has been shown to be differentially expressed in musculus longissimus muscle of low-marbled and high-marbled steer groups [8]. A number of studies showed that Akirin2 is associated with marbling based on single nucleotide polymorphisms analysis and may be considered as a positional functional candidate for the gene responsible for marbling [912]. …”
Section: Introductionmentioning
confidence: 99%
“…At genomic level, studies carried out in beef cattle suggest that IMF could be influenced by a large number of genes . Nevertheless, studies in Japanese Black cattle have reported genomic markers with large effects on IMF or marbling score around the SCD, FASN, AKIRIN2, EDG1 and RPL27A genes (Gotoh et al, 2014;Sukegawa et al, 2014). Genomic markers on the genes SCD and FASN have been incorporated into a breeding programme of this breed to select elite sires (Gotoh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%